2015
DOI: 10.1115/1.4030622
|View full text |Cite
|
Sign up to set email alerts
|

Passive Dynamics Explain Quadrupedal Walking, Trotting, and Tölting

Abstract: This paper presents a simplistic passive dynamic model that is able to create realistic quadrupedal walking, tölting, and trotting motions. The model is inspired by the bipedal spring loaded inverted pendulum (SLIP) model and consists of a distributed mass on four massless legs. Each of the legs is either in ground contact, retracted for swing, or is ready for touch down with a predefined angle of attack. Different gaits, that is, periodic motions differing in interlimb coordination patterns, are generated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 30 publications
3
27
0
Order By: Relevance
“…In normal walk there is a difference in the depth of the midstance dip in the vertical ground reaction force curve between forelimbs and hindlimbs (deeper for the hindlimbs). In a modeling study this could only be explained when taking the head dynamics into account (Gan et al, 2016). Further, at walk the horse moves with substantially less muscle activity in the lower back and abdomen (Wakeling et al, 2007;Zsoldos et al, 2010), and with larger lateral movement of the body center of mass, compared to trot (Buchner et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…In normal walk there is a difference in the depth of the midstance dip in the vertical ground reaction force curve between forelimbs and hindlimbs (deeper for the hindlimbs). In a modeling study this could only be explained when taking the head dynamics into account (Gan et al, 2016). Further, at walk the horse moves with substantially less muscle activity in the lower back and abdomen (Wakeling et al, 2007;Zsoldos et al, 2010), and with larger lateral movement of the body center of mass, compared to trot (Buchner et al, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…This connection is readily apparent when a legged robot moves in a way that maximizes its energetic economy. Model based studies have shown that robots moving in this way take advantage of their natural dynamics [1], [2] (the intrinsic morphologically based motions that result from the interplay of gravity, inertia, and elasticity in the springs). For these models, springs play a key role in explaining the dynamics of legged systems.…”
Section: Introductionmentioning
confidence: 99%
“…In nature, elastic elements are used for energy storage, as return springs, and to cushion impacts [1]. Model-based analyses have shown that compliant legs can explain the dynamics of human walking and running [2], as well as a wide variety of quadrupedal gaits, including walking, trotting, t€ olting, and galloping [3,4]. In all these cases, elastic energy storage enables the recycling of energy and improves energetic economy.…”
Section: Introductionmentioning
confidence: 99%